THE CREATION OF VISITOR SATISFACTION THROUGH QUALITY OF EXPERIENCE IN THE GASTRONOMIC TOURISM AT THE CITY OF BANDUNG, INDONESIA - Vany Octaviany; Ersy Ervina (Institut Pariwisata dan Bisnis Internasional, 2016)
Visitors need something more than just a delicious meal with a good appearance to be satisfied. They need something they can easily remember when they deal with a gastronomic tourism in the city of Bandung. Something they remember is called experience. Unforgettable experience will produce an unforgettable memory, making the Visitors recall their past experience. Quality of experience can affect visitor satisfaction through the impression given by the gastronomic product attributes. But today, the quality of experience is considered to be unable to create satisfaction as sustainable strategy, because usually the gastronomic tourism managers prefer improving ‘taste’ to creating a good impression in the minds of Visitors. A good impression is able to lead the visitors to return, even invite others to come along to the city of Bandung. Therefore, this study was aimed at examining the creation of visitor satisfaction through the quality of experience at a gastronomic tourism in Bandung. This study used a quantitative method. The data analysis techniques included regression analysis. The results showed that the quality of experience is able to create a visitor satisfaction by 60.1%. The highest score is given on the impression perceived during the visit to the gastronomic tourism area.